THE SENSE OF BELONGING IN EDUCATION, A PILLAR FOR THE TRANSFORMATION OF TABASCO - Aguilar, Landy Patricia (Cinzontle, 2025)
Sense of belonging refers to the human emotional need to affiliate with and be accepted by members of a group.; They are part of it. This allows us to develop pride, pride about what we are, in our roots; with this feeling, people try to care for and preserve their environment in such a way that he helps to make their own community develop, they participate positively in its changes, helps the governments. However, if we not promote and open doors to learning, teaching and disseminating our traditions and customs, we have a society disinterested in its surroundings and environment that tries to find other groups to integrate. he. This is why it is important to promote our history and traditions in our basic education and to involve citizens respecting their culture to ensure the success in the development of our communities and cities.